"Tegen de verdrukking in" : Amnesty Filmfestival, Soeterijn; vooruitlopend op de conferentie in Beijing 1995 - Crijns, Gemma.
"Tegen de verdrukking in" : Amnesty Filmfestival, Soeterijn; vooruitlopend op de conferentie in Beijing 1995.